Foreign Burglars: Primary Results of an Interview Study with Arrested Offenders in Germany - Wollinger, Gina Rosa; Jukschat, Nadine (International Journal of Criminology and Sociology, 2017)
Given that the domestic burglary rate in Germany has been on the rise for years, there is currently a huge debate in political arenas and in the media concerning the offenders—especially foreign offenders. However, there is little specific research on burglars, particularly foreign burglars. This paper reports on the main results of a qualitative interview study with convicted foreign offenders in Germany. We conducted 30 narrative-biographical interviews with offenders from 15 different countries. The findings suggest the stereotype of foreign burglars in high-crime gangs is too one-dimensional. Moreover, there is a large range of different motives, biographical backgrounds, and modi operandi. Further, results show that specific circumstances in Germany support the behavior of foreign criminal, such as accommodation possibilities from contacts already living in Germany, or the availability of local fences (i.e. receivers of stolen goods).